2015
DOI: 10.1002/mabi.201500191
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Osteogenecity Enhanced by a Porous Gelatin Sponge in a Critical‐Sized Rat Calvaria Defect

Abstract: The gelatin (Gel) powders, derived from acidic and basic extractions of porcine dermis (referred to as AE and BE), were processed for the porous sponge preparation. The disks, which were less than or greater than 500 μm in diameter [small (S) and large (L) pores, respectively] in both extractions and had an interconnected structure respectively, were implanted in critical-sized defects (CSD) of rat calvaria for 4 and 8 weeks to analyze the bone repair capability. Only the AE-S disk induced bone formation (over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…8). 53 It is probable that the ability of gelatin itself 53 should contribute enhancing bone formation by OCP/Gel more than that by OCP granules alone (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…8). 53 It is probable that the ability of gelatin itself 53 should contribute enhancing bone formation by OCP/Gel more than that by OCP granules alone (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that gelatin molecule has a cellular binding motif and the reconstituted gelatin has been used as a biomedical material as well as collagen . A recent study indicated that Gelatin prepared in specific condition induces orthotopic bone formation in critical‐sized defect of rat calvaria . However, it is recognized that Gelatin sponge does not positively induce the bone formation usually .…”
Section: Discussionmentioning
confidence: 99%
“…38 A recent study indicated that Gelatin prepared in specific condition induces orthotopic bone formation in critical-sized defect of rat calvaria. 28 However, it is recognized that Gelatin sponge does not positively induce the bone formation usually. 39 This is because active molecules, such as bone morphogenetic proteins, are included in Gelatin in tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin is a partial hydrolysis product of native collagen and characterized by non-toxicity, non-carcinogenicity, biocompatibility, and biodegradability 1 3 ; gelatin is widely used in the pharmaceutical and medical fields, such as in wound dressing materials 4 , 5 , tissue engineering scaffolds 6 8 , and drug delivery carriers 9 , 10 . Gelatin can be prepared in a spongy form to be suitable for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%